Penerapan Pembelajaran Aktif (Active Learning) Dengan Strategi Course Review Horay (CRH) Pada Materi Operasi Hitung Bilangan Bulat Menggunakan Media Gambar Mantra Bilangan Bulat di Siswa Kelas V MI Islamiyah Daliwangun Tahun Pelajaran 2013/2014 - Thohir, Anas; Fridayanti, Rima Yuni (saintis, 2016)
The purpose of this study was to determine the effectiveness of the application of active learning model with a strategy CRH using media Figure Mantra Integer in terms of: (a) the studentsâ activities, (b) the teacherâs activities, (c) the studentsâ response, and (d) the studentsâ mastery of learning, on the subject of Â integer arithmetic operations in MI Islamiyah Daliwangun-Sugio-Lamongan in the academic year of 2013-2014. The subjects in this study were the fifth gradersin sum of 12 students. The data collection techniques used were observations, questionnaires and tests. The results of data analysis showed that the activity of the students was 95%, so in this study was said to be effective from the studentsâ activity criteria. Observations of teacherâs activities obtained livelines teacher of 96.43%, resulting in learning was said to be effective from teacherâs activity criteria. Results of student questionnaire responses obtained positive responses of students of 89.29%, resulting in effective learning was said to be seen from the percentage of positive responses of students. The mastery learning students of 91.67%, resulting in learning was said to be effective from classical learning completeness students. Based on the results, it could be concluded that active learning strategies using media CRH Figure Mantra Integer effectively applied to the subject of Operation Count Integer in fifth graders of MI Islamiyah Daliwangun- Sugio-Lamongan in the academic year of 2013-2014.